IMPLEMENTATION OF ISSUANCE OF BIRTHDATES OF CHILDREN OUT OF MARRIED AS CIVIL RIGHTS IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF MEDAN CITY - Maria Rosalina, Nur Aisyah Fitri (NOMOI Law Review, 2020)
The management of birth certificates for legitimate children and children outside of marriage, at the Medan City Civil Registry Service is divided into 2 (two), namely birth certificates based on the age of birth from 0 to 60 days of age and 60 days of age and above.The procedure and terms of the birth certificate legitimate child ismengisi form and attach a photocopyof ID card of parents,family card,birth certificate,marriage certificate (Akt,amarriage),KTP witnessesandto children outside the mating plus a statement of absolute liabilityon the truth of pahusband and wife and the correctness of birth data.The implementation of the requirements and procedures for issuing birth certificates for children outside of wedlock, if linked to theimplementationtheoryof thecontent of policyput forward by Merilee S. Grindle, and connected with the theory of human rights, namely thepositivist theory, is already dilaksanakan.Hambatanissuance of birth certificates of children outside the mating according to respondents in Dukcapil no barriers, but by the community respondents had hambatan.Mengatasi constraints, Department of Population and Civil Registration Medan city has a network of interneton linethat mostlinksinthe whole Indonesia, and put upan information board.The conclusion is that the procedures and requirements for the issuance ofbirth certificates for legitimate and unmarried children as civil rights of childrenat the Medan City Civil Registry Officehave beencarried out in accordance with the Child Protection Law, Population Administration Law,Presidential Decree No.12 of 1983, andPerpres No.96 of 2018.Suggestions for thegovernment should be to implement a policy not to charge fees and to simplify services in the management and issuance of birth certificates for children, especially children outside of wedlock, so that the civil rights of children outside of marriage to have birth certificates can be fulfilled.Keyword:Birth Certificates Excluding Married Children,Office of Population and Civil Registration Medan